Three‐Dimensional sp2 Carbon‐Linked Covalent Organic Frameworks as a Drug Carrier Combined with Fluorescence Imaging. Issue 17 (21st June 2022) - Liao, Li; Zhang, Zerong; Guan, Xinyu; Li, Hui; Liu, Yaozu; Zhang, Minghao; Tang, Bin; Valtchev, Valentin; Yan, Yushan; Qiu, Shilun; Yao, Xiangdong; Fang, Qianrong
Comprehensive Summary: Three‐dimensional (3D) covalent organic frameworks (COFs) are crystalline porous polymers with potential in numerous high‐tech applications, but the linkages involved in their synthesis are still rather limited. Herein, we report novel 3D sp 2 carbon‐linked COFs fabricated by the formation reaction of C=C bonds and their application in fluorescence imaging. These new COFs, namely JUC‐580 and JUC‐581, show high stability and excellent light‐emitting properties in solid state and dispersed in various solvents. Furthermore, we investigate the potential application of JUC‐581 as a drug carrier combined with fluorescence imaging. These results indicate that 3D sp 2 carbon‐linked COFs are not only potential drug‐loaded and sustained release materials but also promising cell fluorescent stains. This study thus expands the structural categories of 3D COFs based on different linkages, and promotes their prospective applications for biomedicine and fluorescent materials. Abstract : Two novel 3D sp 2 carbon‐linked COFs fabricated by the formation reaction of C=C bonds were designed and synthesized, which show high stability, excellent light‐emitting property, and promising application as a drug carrier combined with fluorescence imaging.